From Green Competence to Superior Performance: Bridging Pro-Environmental Behavior in the Hotel Ecosystem - C Susmono Widagdo; Bambang Guritno; Refal Prayogi; Kamelita Anggraeni; Dyah Palupiningtyas (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of competence on employee performance, the effect of pro-environmental behavior on employee performance, and the mediating role of pro-environmental behavior in the relationship between competence and employee performance at Oak Tree Hotel Semarang which has implemented the green hotel concept. The research used a quantitative approach with a survey method involving 109 employees selected using purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The results showed that competence has a positive and significant effect on employee performance, pro-environmental behavior has a positive and significant effect on employee performance, and pro-environmental behavior partially mediates the relationship between competence and employee performance. These findings imply that to improve employee performance, hotel management needs to focus on developing employee competencies in environmental aspects and creating an organizational climate that supports pro-environmental behavior. This research contributes to the development of green hotel management literature by revealing the mechanism that connects competence, pro-environmental behavior, and employee performance.